Analisis Kinerja Pegawai Di Rumah Sakit Ibu Dan Anak (RSIA) “X” Pondok Bambu Jakarta Timur Tahun 2020 - Putri, Muthya Etikasari; Linda, Ony; Zagladin Jacoeb, Teuku Nebrisa; Umniyatun, Yuyun (Journal of Religion and Public Health, 2022)
This study aims to analyze performance and see the relationship between work ability, motivation and work environment with employee performance at the “X” Mother and Child Hospital (RSIA), Pondok Bambu, East Jakarta, 2020. This research is a quantitative analytic study using a cross sectional design. . The population of this study were all 114 employees at SamMamrie Basra Hospital. The sample in this study amounted to 65 employees consisting of paramedical and non-medical employees using stratified random sampling techniques. The data used are primary data using a questionnaire in the form of google form. Data analysis using chi square test. The univariate results of the employee performance are quite good as many as 48 people (73.8%),the ability to work employees with results that are less capable is 35 people (53.8%), motivated employee motivation as much as 44 people (67.7%),then the work environment of employees is good as many as 41people (63.1%). Based on the bivariate results, there is a significant relationship between work ability and employee performance (P = 0.039), motivation with employee performance (P = 0.016). work environment with employee performance (P = 0.027). The advice given to RSIA “X” is tothe provision of training and development programs can be distributed properly so that all employees get it, giving awards in the form of praise, take firm action and impose sanctions in the form of warnings and warning letters, and make a best employee of the month. Keywords: Performance, Employee, HospitalAbstrak Penelitian ini bertujuan untuk menganalisis kinerja dan melihat hubungan kemampuan kerja, motivasi dan lingkungan kerja dengan kinerja pegawai di Rumah Sakit Ibu dan Anak (RSIA) “X” Pondok Bambu Jakarta Timur Tahun 2020. Penelitian ini merupakan analitik kuantitatif dengan menggunakan desain cross sectional. Populasi penelitian ini ialah seluruh pegawai di RSIA “X” berjumlah 114 pegawai. Sampel pada penelitian ini berjumlah 65 pegawai terdiri dari pegawai paramedis dan non medis dengan menggunakan teknik stratified random sampling. Data yang digunakan ialah data primer dengan menggunakan kuesioner dalam bentuk google form. Analisis data menggunakan uji chi square. Hasil univariat kinerja pegawai cukup baik sebanyak 48 orang ( 73,8%), kemampuan kerja pegawai dengan hasil kurang mampu sebanyak 35 orang (53,8%), motivasi pegawai merasa termotivasi sebanyak 44 orang (67,7%), kemudian lingkungan kerja pegawai baik sebanyak 41 orang (63,1%). Berdasarkan hasil bivariat terdapat hubungan yang signifikan kemampuan kerja dengan kinerja pegawai (P=0,039), motivasi dengan kinerja pegawai (P=0,016). lingkungan kerja dengan kinerja pegawai (P=0,027). Saran yang diberikan kepada RSIA “X” yaitu pada pemberian program pelatihan dan pengembangan dapat didistribusikan dengan baik agar seluruh pegawai mendapatkannya, pemberian penghargaan berupa pujian atau insentif bagi pegawai berprestasi, menindak tegas maupun memberi sanksi  berupa teguran dan SP, serta membuat best employee of the month.Kata Kunci: Kinerja, Pegawai, Rumah Sakit